Collagen and Eosinophils in Jenny's Endometrium: Do They Differ With Endometrial Classification? - Miró, Jordi; Gutiérrez-Reinoso, Miguel; Silva, Joana Aguiar da; Fernandes, Carina; Rebordão, Maria Rosa; Alexandre-Pires, Graça; Catalán, Jaime; Ferreira-Dias, Graça (Frontiers in Veterinary Science, 2020)
Collagen fibers and inflammatory cells are the basis for jenny endometrium Kenney and Doig's classification developed for the mare. The infiltration of a large number of eosinophils in the jenny endometrium is intriguing. Eosinophil and fibroblast produced IL33, which has been related to fibrosis development and chronicity. This work on the endometrium consisted of (i) quantification of collagen type I (COL1A2), type III (COL3A1), and IL33 transcripts; (ii) histological localization and quantification of COL1 and COL3 proteins; and (iii) eosinophil and neutrophil count and correlation with collagen area and IL33 transcripts. Localization of COL protein in the jenny endometrium was also compared to the mare endometrium. As fibrosis increased, eosinophil and neutrophil count decreased (P < 0.05). A 5-fold increase in IL33 transcripts was noted from categories IIA to III. There was a tendency toward a positive correlation between eosinophil count and IL33 transcripts in category IIA endometrium (P = 0.055). Neither transcripts of COL1A2 nor COL3A1 nor the areas of COL1 or COL3 differed with endometrial categories. Unlike for the mare, and regardless of the jenny endometrium classification, COL3 was always found to different extents in the stratum compactum, while COL1 was mainly present in deep stroma. As fibrosis progressed in the mare, an extensive increase in COL1 fibers was notorious under the surface epithelium. Correlations between neutrophil count and COL1 and COL3 areas were observed in the jenny endometrium, although no correlation was found for eosinophil count. Neutrophil count positive correlation with the COL1 area and negative correlation with the COL3 area in endometria with mild lesions suggest that neutrophils in the jenny endometrium may be involved in fibrogenesis. In addition, when eosinophilia subsides, the endometrium reacts with fibrosis establishment, which could be stimulated by the pro-fibrotic cytokine IL33, whose release might then be ascribed to fibroblasts. Further studies are needed to analyze the effect of the presence of COL3 next to the surface epithelium in the stratum compactum, or around the endometrial glands on jenny's endometrial function and fertility.